Rates of reoperation after breast conserving cancer surgery in Western Australia before and after publication of the SSO-ASTRO margins guideline. - Marinovich, Luke; Saunders, Christobel; Pereira, Gavin; Houssami, Nehmat (Elsevier, 2023)
Background: A 2014 SSO-ASTRO guideline on surgical margins aimed to reduce unnecessary reoperation after breast conserving surgery (BCS). We investigate whether publication of the guideline was associated with a reduction in reoperation in Western Australia (WA). Methods: In this retrospective, population-based cohort study, cases of newly-diagnosed breast cancer were identified from the WA Cancer Registry. Linkage to the Hospital Morbidity Data Collection identified index BCS for invasive cancer between January 2009 and June 2018 (N = 8059) and reoperation within 90 days. Pre-guideline (2009–2013) and post-guideline (2014–2018) reoperation proportions were compared, and temporal trends were estimated with generalised linear regression. Results: The pre-guideline reoperation proportion was 25.8% compared with 21.7% post-guideline (difference −4.0% [95% CI —5.9, −2.2, p < 0.001], odds ratio [OR] 0.80 [95% CI 0.72, 0.89, p < 0.001]). Absolute reductions were similar for repeat BCS (16.3% versus 14.6%; difference −1.8% [95% CI —3.4, −0.2, p = 0.03]) and conversion to mastectomy (9.4% versus 7.2%; difference −2.2% [95% CI —3.4, −1.0, p < 0.001]). Over the study period, there was an annual absolute change in reoperation of −0.8% (95% CI —1.2, −0.5, p < 0.001). Accounting for this linear trend, the difference in reoperation between time periods was −0.5% (95% CI —4.3, 3.3; p = 0.81), reflecting a non-significant reduction in conversion to mastectomy. Conclusions: Comparisons of pre- versus post-guideline time periods in WA showed reductions in reoperation that were similar to international estimates; however, an annual decline in reoperation predated the guideline. Analyses that do not account for temporal trends are likely to overestimate changes in reoperation associated with the guideline.